Effect of Green synthesized silver oxide nanoparticle on biological hydrogen production - Yildirim, Oznur; Tunay, Dogukan; Ozkaya, Bestami; Demir, Ahmet (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
Investigation of the effect of different nanoparticles on dark fermentation is very popular nowadays. Among the nanoparticle production methods, the use of nanoparticles produced by the green synthesis method, which is more environmentally friendly, is important for a sustainable environment. This study investigated the effect of green synthesized silver oxide nanoparticles on bio-hydrogen yield. Nanoparticle synthesis was carried out by using Chlorella sp. microalgae as a reducing agent. SEM, EDX and UV-Visible spectrum analyzes were performed for the characterization of the synthesized nanoparticles. The synthesized silver nanoparticles have a uniform structure and an average particle size of 85 nm. Hydrogen production performance by Clostridium sp. was evaluated using different ratios of produced nanoparticles (100-600 mg/L). The addition of 400 mg/L nanoparticles increased the production of dark fermentative bio-hydrogen by 17% compared to the control group. The highest hydrogen yield was 2.44 mol H-2/mol glucose.(C) 2021 Published by Elsevier Ltd on behalf of Hydrogen Energy Publications LLC.
Keywords: Nanoparticle; Bio-hydrogen; Silver nanoparticle; Clostridium sp; Microalgae; BIOHYDROGEN PRODUCTION; ENTEROBACTER-CLOACAE; BIOSYNTHESIS; FERMENTATION; ENHANCEMENT; Chemistry; Electrochemistry; Energy & Fuels